Can Movement be Depicted? - Young, Nick; Calabi, Clotilde (Phenomenology and Mind, 2018)
It is natural to describe many pictures as of movement. We might for example say that a painting is of a horse rearing up, or a dog scurry along the pavement. The topic of this paper is how this “of” should be understood. Can a static picture depict movement, or is movement merely represented by, or suggested by, pictures, in some non-pictorial way? We argue that movement can be depicted and not merely represented. We examine three different views put forward by Le Poidevin, and use his third as a basis for our own view of movement depiction, which is a version of Hopkins’s experienced resemblance theory of depiction.